A Note on an Infraspecific Taxon of Albizia chinensis (Osbeck) Merrill - Sahni, K. C.; Chawala, S.; Bennet, S. S. R. (Indian Forester, 1977)
A new combination, Albizia chinensis var. smithiana (Roxb.) Sahni, Chawla and Bennet, is proposed for A. stipulata var. smithiana (Roxb.) Praia, as the correet name. for A. stipulata Boiv. Is A. chinensis (Osbeck) Merr. From the original description of Roxburgh it is evident that the large stipuled plants should be called var. smithiana and not the small stipuled plants as Prain and later botaniots have done.